Review paper High-dose-rate brachytherapy as monotherapy for prostate cancer: technique, rationale and perspective - Yoshioka, Yasuo; Suzuki, Osamu; Otani, Yuki; Yoshida, Ken; Nose, Takayuki; Ogawa, Kazuhiko (Journal of Contemporary Brachytherapy, 2014)
High-dose-rate (HDR) brachytherapy as monotherapy is a comparatively new brachytherapy procedure for prostate cancer. Although clinical results are not yet mature enough, it is a highly promising approach in terms of potential benefits for both radiation physics and radiobiology. In this article, we describe our technique for monotherapeutic HDR prostate brachytherapy, as well as the rationale and theoretical background, with educational intent.